Oliceridine and its potential to revolutionize GI endoscopy sedation - Basavana Goudra; Preet Mohinder Singh (Saudi Journal of Anaesthesia, 2020)
Providing sedation to patients undergoing gastrointestinal (GI) endoscopy is a controversial and emotive issue. The mainstay of sedation is propofol, whose administration is within the sole jurisdiction of anesthesia providers, at least in the USA. Attempts have been made to seize the authority by the GI community. One of the first attempts was the use of the prodrug of propofol –fospropofol. However, as the drug has a similar adverse effect profile as propofol in terms of respiratory depression, the FDA did not approve its use by providers other than those trained in airway management. Sedasys® was the next attempt, which was a computer-assisted personalized sedation system. As a result of insufficient sedation that could be provided with the device, although very successful in research settings, it was not a commercial success. It seems that remimazolam is the next effort in this direction. It is likely to fail in this regard unless its respiratory depressant properties and failure rates could be addressed. G protein-biased μ-receptor agonists are a new class of opioids exhibiting analgesic properties similar to morphine without equivalent respiratory depressant properties. Oliceridine is the prototype. As a result, the drug can be additive to midazolam or remimazolam and allow screening colonoscopy to be comfortably completed without the need for propofol. For an anesthesia provider, the administration of oliceridine can eliminate the need for drugs such as fentanyl that add to the respiratory depressant properties of propofol. As a result, oliceridine has the potential to render the sedation for GI endoscopy procedures both safe and cost-effective.